2016
DOI: 10.1002/ijch.201600110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Right‐Side Structure of Type B Physalins

Abstract: We present a full account of our synthetic studies on the racemic DEFGH‐ring moiety of physalins, featuring domino ring transformation of a tricyclic key intermediate. We also report the results of a detailed mechanistic examination of the domino ring transformation, as well as a reoptimization of the 2,3‐Wittig rearrangement and methylation steps. Furthermore, we have newly established a method for the preparation of an optically active synthetic intermediate by enzymatic kinetic resolution. Our work provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The HRESIMS and NMR data of 4 and 5 provided the molecular formula C 28 H 32 O 14 S, indicating 13 degrees of unsaturation. The 1 H NMR spectrum exhibited signals typical of a mixture of two physalin-type withanolides and contained those due to six methyl groups [δ H 1.90 (3H, s), 1.89 (3H, s), 1.56 (3H, s), 1.21 (3H, s), and 0.93 (6H, s)], H 2 -27 of the C-25(27) exocyclic methylene moiety [δ H 6.53 (1H, brs) and 5.68 (1H, brs)], and oxymethylene protons [δ H 4.40 (1H, dd, J = 13.5, 4.6 Hz) and 3.70 (1H, d, J = 13.5 Hz)], suggesting some similarities between this mixture and the known interconvertible forms of physalin F ( 8 ) . The 13 C NMR spectrum of the mixture of 4 and 5 assigned with the help of HSQC data revealed 56 carbons including typical signals for four ketone carbonyls (δ C 213.6, 212.0, 211.7, and 209.5), four lactone carbonyls (δ C 174.3, 173.8, 170.2, and 165.0), and six methyls (δ C 27.9, 25.9, 22.4, 21.6, 11.0, and 10.7).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The HRESIMS and NMR data of 4 and 5 provided the molecular formula C 28 H 32 O 14 S, indicating 13 degrees of unsaturation. The 1 H NMR spectrum exhibited signals typical of a mixture of two physalin-type withanolides and contained those due to six methyl groups [δ H 1.90 (3H, s), 1.89 (3H, s), 1.56 (3H, s), 1.21 (3H, s), and 0.93 (6H, s)], H 2 -27 of the C-25(27) exocyclic methylene moiety [δ H 6.53 (1H, brs) and 5.68 (1H, brs)], and oxymethylene protons [δ H 4.40 (1H, dd, J = 13.5, 4.6 Hz) and 3.70 (1H, d, J = 13.5 Hz)], suggesting some similarities between this mixture and the known interconvertible forms of physalin F ( 8 ) . The 13 C NMR spectrum of the mixture of 4 and 5 assigned with the help of HSQC data revealed 56 carbons including typical signals for four ketone carbonyls (δ C 213.6, 212.0, 211.7, and 209.5), four lactone carbonyls (δ C 174.3, 173.8, 170.2, and 165.0), and six methyls (δ C 27.9, 25.9, 22.4, 21.6, 11.0, and 10.7).…”
Section: Results and Discussionmentioning
confidence: 99%
“…We tried coupling the adamantyl alkyl group with 6 , but all attempts failed. Thus, we commenced the synthesis of 5d from bicyclic enone 15 , (see Scheme A) and investigated the direct addition of the 4-(1-adamantyl)-1-butyne unit 16 to enone 15 . In the previous synthesis, the addition of lithium TMS-acetylide in the presence of CeCl 3 proceeded in high yield (for the synthesis of 6 ). , However, no reaction occurred with the corresponding acetylide generated from 16 , and the starting material was quantitatively recovered.…”
mentioning
confidence: 99%
“…Thus, we commenced the synthesis of 5d from bicyclic enone 15 , (see Scheme A) and investigated the direct addition of the 4-(1-adamantyl)-1-butyne unit 16 to enone 15 . In the previous synthesis, the addition of lithium TMS-acetylide in the presence of CeCl 3 proceeded in high yield (for the synthesis of 6 ). , However, no reaction occurred with the corresponding acetylide generated from 16 , and the starting material was quantitatively recovered. We found that the desired nucleophilic 1,2-addition was accelerated in the presence of N -methylpyrrolidone (NMP) instead of CeCl 3 as an additive, and 17 was obtained in 92% yield.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In step 3, the skeletons of physalins (Types I and II) were produced from 24-methylene cholesterol [ 13 , 16 , 17 ]. Furthermore, the racemic DEFGH-ring moiety of physalins (Type I) is synthesized through enzymatic kinetic resolution [ 18 ]. The intermediate physalins were synthesized by domino ring transformation, a reoptimization of the 2,3-wittig rearrangement, and methylation steps.…”
Section: Structural Analysismentioning
confidence: 99%